Rapid removal of fine particles from mine water using sequential processes of coagulation and flocculation - Jang, M.; Lee, H.J.; Shim, Y. (2010)
The processes of coagulation and flocculation using high molecular weight long-chain polymers were applied to treat mine water having fine flocs of which about 93 of the total mass was less than 3.02 m, representing the size distribution of fine particles. Six different combinations of acryl-type anionic flocculants and polyamine-type cationic coagulants were selected to conduct kinetic tests on turbidity removal in mine water. Optimization studies on the types and concentrations of the coagulant and flocculant showed that the highest rate of turbidity removal was obtained with 10 mg L-1 FL-2949 (coagulant) and 12 mg L-1 A333E (flocculant), which was about 14.4 and 866.7 times higher than that obtained with A333E alone and that obtained through natural precipitation by gravity, respectively. With this optimized condition, the turbidity of mine water was reduced to 0 NTU within 20 min. Zeta potential measurements were conducted to elucidate the removal mechanism of the fine particles, and they revealed that there was a strong linear relationship between the removal rate of each pair of coagulant and flocculant application and the zeta potential differences that were obtained by subtracting the zeta potential of flocculant-treated mine water from the zeta potential of coagulant-treated mine water. Accordingly, through an optimization process, coagulation-flocculation by use of polymers could be advantageous to mine water treatment, because the process rapidly removes fine particles in mine water and only requires a small-scale plant for set-up purposes owing to the short retention time in the process.